A three-phase bidirectional variable speed drive: an experimental validation for a three-phase induction motor - Machado, Luís Filipe Carvalho (2020)
This paper presents the implementation and subsequent experimental verification of an electronic variable speed drive (VSD) for driving an induction motor, which is composed by a three-phase ac-dc converter on the grid-side and by a three-phase dc-ac converter on the motor-side. With the proposed solution, besides driving the motor, it is possible to mitigate power quality problems on the grid-side (e.g., current harmonics and power factor) associated with the use of diode-bridge ac-dc converters in the conventional VSDs. Besides, with the proposed solution, a bidirectional operation is possible, allowing to deliver to the power grid the energy generated in motor braking processes. As demonstrated along the paper, with the proposed VSD, it is possible to control the motor speed (including the rotation direction), and the operation with sinusoidal currents and unitary power factor on the grid-side. A laboratory prototype was developed, permitting to perform an experimental validation and prove the main functionalities of the VSD.